2022
DOI: 10.3390/cells11142252
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Human Immature Dental Pulp Stem Cells Observed in Mouse Model for Acquired Aplastic Anemia

Abstract: Aplastic anemia (AA) is a rare and serious disorder of hematopoietic stem cells (HSCs) that results in the loss of blood cells due to the failure of the bone marrow (BM). Although BM transplantation is used to treat AA, its use is limited by donor availability. In this sense, mesenchymal stem cells (MSCs) can offer a novel therapeutic approach for AA. This is because the MSCs contribute to the hematopoietic niche organization through their repopulating. In our study, we used the human immature dental pulp stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Inada et al transplanted pancreatic β-like cells obtained after induction of DPSC into a rat model of diabetes mellitus and obtained good therapeutic results ( Inada et al, 2022 ). Gonzaga et al used DPSC for intraperitoneal treatment of aplastic anemia model mice and found that DPSC provided rapid support for hematopoiesis and hematopoiesis recovered after 6 months ( Gonzaga et al, 2022 ). Wenceslau et al used DPSC intravenously to treat rats with Huntington’s chorea model, resulting in a significant increase in the secretion of brain-derived neurotrophic factor, which effectively promoted neuroprotection and neurogenesis ( Wenceslau et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inada et al transplanted pancreatic β-like cells obtained after induction of DPSC into a rat model of diabetes mellitus and obtained good therapeutic results ( Inada et al, 2022 ). Gonzaga et al used DPSC for intraperitoneal treatment of aplastic anemia model mice and found that DPSC provided rapid support for hematopoiesis and hematopoiesis recovered after 6 months ( Gonzaga et al, 2022 ). Wenceslau et al used DPSC intravenously to treat rats with Huntington’s chorea model, resulting in a significant increase in the secretion of brain-derived neurotrophic factor, which effectively promoted neuroprotection and neurogenesis ( Wenceslau et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the MSCs currently used for clinical treatment are primarily derived from adult or fetal tissues; these MSCs have some limitations including low purity, insufficient sources, high cell senescence, and reduced multidirectional differentiation and proliferation capacity (Fujii et al 2018 ). In addition, tissue-derived MSCs lack TERC expression, and the regulation of telomerase genes is affected by a variety of factors (Gonzaga et al 2022 ); consequently, the function of these MSCs is restricted. Telomere haploinsufficiency is a key problem; its occurrence leads to a lack of telomere-related gene products, weakened TERC activity, insufficient cell regenerative ability, and the failure of MSCs libraries.…”
Section: Clinical Strategies For Improving Terc Function Via Cell Rep...mentioning
confidence: 99%
“…The MSC phenotype of these cells was con rmed using the criteria de ned by the International Society for Cell Therapy (ISCT) (Dominici et al, 2006). The hIDPSCs employed in this study are CD105-, CD73-and CD90-positive, and CD45-, CD34-, CD11b-, and HLA-DR-negative, as previously described by us Gonzaga et al, 2022;Kerkis et al, 2006;Wenceslau et al, 2022). The cell manufacturing process was performed according to the good manufacturing practices (GMP) required by the Brazilian Health Regulatory Agency (ANVISA, RDC 508/21) for advanced therapy products.…”
Section: Isolation Culture and Characterization Of Hipdscs (Nestacell...mentioning
confidence: 99%
“…In this sense, cumulative evidence have showed that human immature dental pulp stromal/stem cell (hIDPSCs), a special type of adult MSC, isolated from the deciduous teeth of children aged between six to 12 years, is a potential candidate for the treatment of neurodegenerative disorders (Araldi et al, 2022a;Kerkis et al, 2006). This is because, due to their ectomesenchymal origin (neural crest), the hIDPSCs naturally produce and secretes a plethora of neural factors, including nesting (a neural stem/progenitor cell marker) (Kerkis and Caplan, 2012;Suzuki et al, 2010) and brain-derived neurotrophic factor (BDNF, which is found downregulated in patients with Huntington's disease -HD) (Gonzaga et al, 2022;Wenceslau et al, 2022), but showing all the criteria for de ning multipotent MSC proposed by the International Society for Cellular Therapy (Choudhery et al, 2022;Dominici et al, 2006).…”
Section: Introductionmentioning
confidence: 99%